2018
DOI: 10.1021/acs.langmuir.8b03016
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Interfacial Effects on Surface Nanobubbles without Pinning Using Molecular Dynamics Simulation

Abstract: We investigated how the stability of aqueous argon surface nanobubbles on hydrophobic surfaces depends on gas adsorption, solid−gas interaction energy, and the bulk gas concentration using molecular dynamics simulation with the SPC/E water solvent. We observed stable surface nanobubbles without surface pinning sites for longer than 160 ns, contrary to previous findings using monoatomic Lennard-Jones solvent. In addition, the hydrophobicity of a substrate has an effect to reduce the requirement degree of oversa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 52 publications
2
24
1
Order By: Relevance
“…And what is the evidence that substrate hydrophobicity influences stability and dynamics? Molecular simulations have recently demonstrated that substrate hydrophobicity enhances nanobubbles' resilience to dissolution [25], while nucleation experiments with AFM show that the contact angles of nanobubbles increases with substrate hydrophobicity [26], as we predict [21].…”
supporting
confidence: 58%
See 1 more Smart Citation
“…And what is the evidence that substrate hydrophobicity influences stability and dynamics? Molecular simulations have recently demonstrated that substrate hydrophobicity enhances nanobubbles' resilience to dissolution [25], while nucleation experiments with AFM show that the contact angles of nanobubbles increases with substrate hydrophobicity [26], as we predict [21].…”
supporting
confidence: 58%
“…But as the hydrophobicity increases, c à i =c sat → 0 asymptotically, at which limit gas molecules cannot be destabilized by any degree of degassing. Furthermore, the idea that tolerance develops from substrate hydrophobicity has recently been confirmed in molecular dynamics simulations [25]. Finally, the slow approach to c à i =c sat → 0 in the hydrophobic limit in Fig.…”
mentioning
confidence: 60%
“…One is the overestimation of the gas density inside the nanobubbles in STXM observations caused by the existence of an ultradense gas molecule-adsorbed layer underneath them. The formation of the dense adsorbed layers of gas molecules has been reported not only by MD simulations 22,24,40 but also by AFM 40,50–52 and LPEM 53,54 experiments. Our analysis also found that even when the pressure P gas was reduced to 0.2 MPa corresponding to the nanobubbles with a footprint radius of 250 nm and a contact angle of 170°, the peak density inside the adsorbed layer was 37 and 241 kg m −3 for η = 1.0 and 1.5 (shown in ESI Fig.…”
Section: Resultsmentioning
confidence: 94%
“…The top graphene worked as a piston to attain the pressure in the liquid at the atmospheric pressure P 0 = 1 atm, as it has been successfully used in previous studies. 22,38,39 The Lennard-Jones (LJ) energy between the carbon atoms in the bottom graphite and N 2 molecules was changed by multiplying a coupling parameter η = 1.0 or 1.5 to investigate the influence of the solid–gas interaction. The details of the setup of these nanobubble simulations are described in the Methods section.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation